Regulation of Eosinophil and Group 2 Innate Lymphoid Cell Trafficking in Asthma - Larose, Marie-Chantal; Archambault, Anne-Sophie; Provost, Véronique; Laviolette, Michel; Flamand, Nicolas (Frontiers in Medicine, 2017)
Asthma is an inflammatory disease usually characterized by increased Type 2 cytokines and by an infiltration of eosinophils to the airways. While the production of Type 2 cytokines has been associated with TH2 lymphocytes, increasing evidence indicates that group 2 innate lymphoid cells (ILC2) play an important role in the production of the Type 2 cytokines interleukin (IL)-5 and IL-13, which likely amplifies the recruitment of eosinophils from the blood to the airways. In that regard, recent asthma treatments have been focusing on blocking Type 2 cytokines, notably IL-4, IL-5 and IL-13. These treatments mainly result in decreased blood or sputum eosinophil counts as well as decreased asthma symptoms. This supports that therapies blocking eosinophil recruitment and activation are valuable tools in the management of asthma and its severity. Herein, we review the mechanisms involved in eosinophil and ILC2 recruitment to the airways, with an emphasis on eotaxins, other chemokines as well as their receptors. We also discuss the involvement of other chemoattractants, notably the bioactive lipids 5-oxo-eicosatetraenoic acid, prostaglandin D2 and 2-arachidonoyl-glycerol. Given that eosinophil biology differs between human and mice, we also highlight and discuss their responsiveness toward the different eosinophil chemoattractants.